Stop this political circus, we don’t need the clowns - Abd Razak, Dzulkifli (2009)
RECENTLY, a friend told me that the circus is no longer a popular entertainment in his country. I replied that I could appreciate why given the difficult economic situation we are facing today. The circus as a wholesome family outing can be an expensive treat. With a cynical smile, he was quick to quip: "Not that. The politicians have now taken over! Though it lacks professionalism and finesse, it is free." The real circus is out of business for now, came the punch line. In silence, I smiled back politely. It sounded rather familiar, especially of late. Our version might still be a sideshow type of circus, but it is bad enough, considering it has the potential of developing into a fullfledged threering circus as more and more surprises are unveiled each day.